Advancing the security of record management of record management in education using blockchain technology - A. Sekinat Olaniyan; O. Motunrayo Moradeyo; O. Peter Popoola; A. Adekunle Araromi (ZBW - Leibniz Information Centre for Economics, 2023)
Blockchain technology has gained considerable attention due to its unique features including decentralization, security, reliability, and data integrity. Despite this, much is yet to be known about the current state of knowledge and practice regarding using blockchain technology in education. This paper highlight the use cases of blockchain technology in Record management, discuss the major components of Block-chain-based Educational Record management, and then propose a system architecture for advancing the security of result/record database in education using a consortium system to create certificate records on the network. Comparison to related work has shown that block-chain-based record management offers better possibilities for advancing the security of student database record management and transferring information, certificate, or credentials at lesser cost and time.
Keywords: 330; blockchain; educational technology; decentralized Block-certs; consortium